Transorbital impalement by a wooden stick in a 3-year-old child. (2nd September 2015) - Damm, Anders; Lauritsen, Anne Øberg; Klemp, Kristian; Nielsen, Rikke Vibeke
Abstract : We present a case of a 3-year-old girl with a transorbital impalement injury due to a wooden stick penetrating the lower inferior palpebra and progressing through the orbita, after the child jumped from a table and hit a wooden basket containing pieces of exposed stick. CT revealed the stick progressing transorbitally through the medial wall and terminating just below the sella turcica. The stick was successfully removed by neurosurgical and ophthalmological specialists. The eye was subsequently inspected, and showed no pathological findings. The girl was treated with topical chloramphenicol and discharged 2 days later. Follow-up examination 2 months after the trauma demonstrated normal visual acuity and ocular motility, with no diplopia, tearing or pain.